Dr. No [videorecording (Blu-Ray)] - Young, Terence, 1915-1994; Connery, Sean; Andress, Ursula, 1936-; Wiseman, Joseph; Lord, Jack; Lee, Bernard, 1908-1981 (007., 2015)
"James Bond (007) is Britain's top agent and is on an exciting mission, to solve the mysterious murder of a fellow agent. The task sends him to Jamaica, where he joins forces with Quarrel and a loyal CIA agent, Felix Leiter. While dodging tarantulas, "fire breathing dragons" and a trio of assassins, known as the three blind mice. Bond meets up with the beautiful Honey Ryder and goes face to face with the evil Dr. No."